2019
DOI: 10.1021/acs.orglett.9b03674
|View full text |Cite
|
Sign up to set email alerts
|

Ortho/Ipso Alkylborylation of Aryl Iodides

Abstract: This work describes a method for the difunctionalization of aryl iodides to generate polysubstituted arenes via Pd catalysis. The reaction hinges on the unique interplay between norbornene and the metal catalyst to impart a guided ortho C–H alkylation event followed by a programmatic ipso borylation to provide a diverse array of substituted arene products. The utility of this transformation is demonstrated through the functionalization of the boronic ester to a variety of valuable functionalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In a separate study, a complementary Catellani-type ortho methylation/ipso borylation strategy was demonstrated by Smith, where methyl iodide was employed to enable the C(sp 2 )-H methylation/borylation of 2-iodotoluene in 60% yield. 94 The methodology reported by Zhou (vide supra) was also successfully performed on several aryl bromides, an uncommon but synthetically useful development. Dong similarly conducted a Catellani-type C(sp 2 )-H methylation of 2-bromoanisole, in which methyl 4-nitrobenzenesulfonate (MeONs) was utilised as the methylating agent (Scheme 30).…”
Section: Catellani-type Strategies For C(sp 2 )-H Methylationmentioning
confidence: 99%
“…In a separate study, a complementary Catellani-type ortho methylation/ipso borylation strategy was demonstrated by Smith, where methyl iodide was employed to enable the C(sp 2 )-H methylation/borylation of 2-iodotoluene in 60% yield. 94 The methodology reported by Zhou (vide supra) was also successfully performed on several aryl bromides, an uncommon but synthetically useful development. Dong similarly conducted a Catellani-type C(sp 2 )-H methylation of 2-bromoanisole, in which methyl 4-nitrobenzenesulfonate (MeONs) was utilised as the methylating agent (Scheme 30).…”
Section: Catellani-type Strategies For C(sp 2 )-H Methylationmentioning
confidence: 99%